School Mathematics Teachers Are Super Heroes - Allan Leslie White (SEAMEO Regional Centre for QITEP in Mathematics, 2011)
Hollywood has produced many super heroes such as Superman, Batman and Wonder Woman. Recently it released a film titled 'Waiting for Superman' which shows a young boy imprisoned within a system and classroom that does not stimulate his learning while actively destroying his motivation and engagement with the educational process. The film implied the task of fixing the problem was so great that only Superman could fix it. So what are the criteria for a super hero? Firstly it is someone with extraordinary powers beyond those of most mortals. In this paper I will propose that most mathematics teachers meet the criteria and are super heroes who combat the spread of darkness and ignorance of mathematics. I will present evidence to prove that most mild mannered mathematics teachers are really super heroes in disguise. Mathematics teachers have super powers. They have the power to understand and value mathematics, something that is beyond the vast majority of the population. What is the basis of their power? It is their mathematics pedagogical and content knowledge. Not only can they do mathematics, but they can construct a learning environment where their students develop conceptual knowledge and deep learning. They use the latest developments in technology to assist their battle with the forces of darkness and innumeracy. While more mathematics has been invented in the last 50 years than in the preceding years of human development, teachers are expected to keep abreast of this new knowledge. Hollywood may be waiting for Superman, but the real super heroes are every day engaged in the battle to reveal to their students the power and the beauty of mathematics that can transform their lives.